Some doubts about concessions in Brazil: should Brazil shelve its proposed system of forest concessions? - Merry, F.; Amacher, G.S.; Pokorny B.; Lima, E.; Scholz, I.; Nepstad, D.C.; Zweede, C.J. (2003)
The government of Luiz Inacio Lula da Silva of Brazil inherited, in its National Forest Program, a formidable proposal to increase the area designated to national forests (FLONAs) in the Amazon from eight to 50 million hectares by the year 2010. This objective is an ambitious and worthy conservation goal, and one that appears to be holding approval, give or take a few million hectares, within the new government. Attached to this plan, however, is a lingering desire to allow private timber harvesting on FLONAs through a system of forest concessions. The decision of the previous government to adopt concessions was based on the premise that such a program would increase profits from forestry, reduce illegal logging, and increase the adoption of sustainable forest management practices. The current government has taken a more cautious approach, but nonetheless continues to be tied to the idea of timber concessions in FLONAs. In this article, we question the need for concessions and then identify some major concerns should they become a reality. We argue that while expanding FLONAs is a good idea, allowing timber harvests within these forests is a risk that, for now, Brazilian society should not take.